Illustration of the Writing Techniques and the Writing Process According to Nation Students of Adrar University: Ahmed Draia as a Case Study - Lakhrif, Halima; Mahieddine, Rachid (جامعة أحمد دراية أدرار, 2017)
Herein, we intended to highlight some writing techniques that are proposed as a programme in Nation’s book Teaching ESL/EFL Reading and Writing (2009) to enhance the learners’ writing skill. Practically, we limited our study to Nation’s view of writing as a process. Accordingly, we analysed twenty-five (25) students’ written exam papers, randomly collected from different levels and varied modules for assessing to what extent students succeed or fail in implementing the steps of the writing process. We dopted a mixed method (quantitative and qualitative). We concluded that our informants almost failed to do so. Accordingly, the frequency of mistakes was gradually decreasing while assessing the papers moving from the license to the master level. However, some students were brilliant performing good pieces whatever the level is.
من خلال هذا العمل تطرقنا إلى البرنامج المقترح في كتاب نيشن لتحسين فن الكتابة لدى الطلبة تطبيقيا اقتصرت دراستنا على رأي نيشن إزاء الكتابة كأسلوب متسلسل، من أجل ذلك قمنا بالجمع العشوائي لخمس وعشرون ورقة امتحان كتابي لطلبة الإنجليزية لمستويات ومواد مختلفة ودراستها من أجل معرفة إلى أي حد وفقوا أو أخفقوا في كتاباتهم وإتباعهم للأسلوب المقترح من طرف الكاتب. علما أنه تم إتباعا الطريقة المزدوجة لتقييمهم (الكيفية والكمية أو الحسابية). وقد تبين أن معظم الطلبة لم يوفقوا في إتباع الطرق الصحيحة للكتابة مع ملاحظة تحسن في التمكن مرورا إلى لمستوى الدراسي الأعلى مع استثناء بعض الحالات التي تملك المهارة في الكتابة مهما كان المستوى.
Keywords: اللغة الإنجليزية -- المهارات اللغوية -- فنون الكتابة -- الجامعات الجزائرية -- طلبة الجامعات